2015
DOI: 10.1038/npp.2015.227
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic Activation of Adenosine A2A Receptor Signaling in the Dorsomedial Striatopallidal Neurons Suppresses Goal-Directed Behavior

Abstract: The striatum has an essential role in neural control of instrumental behaviors by reinforcement learning. Adenosine A(2A) receptors (A(2A)Rs) are highly enriched in the striatopallidal neurons and are implicated in instrumental behavior control. However, the temporal importance of the A(2A)R signaling in relation to the reward and specific contributions of the striatopallidal A(2A)Rs in the dorsolateral striatum (DLS) and the dorsomedial striatum (DMS) to the control of instrumental learning are not defined. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 48 publications
4
56
0
Order By: Relevance
“…This novel molecular correlate of the RI training and possibly habit formation would be useful in molecular dissecting and monitoring habit formation. Moreover, our detailed analysis of A 2A R-D 2 R heterodimer changes on anterior-posterior axes indicated that the A 2A R-D 2 R heterodimers in the DMS showed more dynamic changes after RI training in agreement with our recent finding that the DMS A 2A R signaling plays a major role in control of instrumental learning (Li et al, 2016). …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This novel molecular correlate of the RI training and possibly habit formation would be useful in molecular dissecting and monitoring habit formation. Moreover, our detailed analysis of A 2A R-D 2 R heterodimer changes on anterior-posterior axes indicated that the A 2A R-D 2 R heterodimers in the DMS showed more dynamic changes after RI training in agreement with our recent finding that the DMS A 2A R signaling plays a major role in control of instrumental learning (Li et al, 2016). …”
Section: Discussionsupporting
confidence: 91%
“…The increased association of the A 2A R-D 2 R heterodimers was seen selectively after the RI schedule (to promote habit), but was not seen in the mice trained by the RR schedule (to promote goal-directed behavior). Genetic and pharmacological studies have implicated several neurotransmitter and neuromodulator receptors take effects on development of goal-directed and habit behaviors, including D 1 R, D 2 R (Yin et al, 2009), CB 1 R (Hilário et al, 2007), NMDAR (Yin et al, 2005), A 2A R (Yu et al, 2009; Li et al, 2016), and Gpr6 (Lobo et al, 2007), by alteration of instrumental behaviors. However, to the best of our knowledge, this is the first report on the molecular marker of habitual formation that is selectively induced by the RI (but not the RR) training schedule.…”
Section: Discussionmentioning
confidence: 99%
“…It can lead to the differential dopaminergic signaling observed in the ventral and dorsal striatum with selective A2AR agonist induced inhibition of D2R signaling in the ventral striatum (Figure 2). The loss of the antagonistic allosteric A2AR-D2R interactions in the dorsal striatopallidal GABA neurons of the dorsal striatum found in cocaine self-stimulation can have an impact on novel habit formation versus goal-directed behavior that remains to be determined [78]. …”
Section: Discussionmentioning
confidence: 99%
“…However, A2ARs appear to have a different role in the dorsal striatum where a striatum-specific A2AR deletion led to selective impairment of habit formation [77]. Later on, it was demonstrated that dorsomedial striatopallidal GABA neurons upon optogenetic activation of their A2ARs diminished goal-directed behavior [78]. Thus, in this circuit, A2AR signaling when linked to reward may favour habit formation.…”
Section: On the Role Of Antagonistic A2a-d2 Allosteric Receptor-rementioning
confidence: 99%
See 1 more Smart Citation